Selecting the Right Virtualization Technology (Solution accelerators. Infrastructure planning and design., 2008)
The objective of this guide is to enable the reader to rapidly and accurately select which Microsoft® virtualization technology or technologies to use for specific scenarios. There are several different forms of virtualization that need to be understood as a basis for making the right technology choice. This guide addresses the decision steps that need to be taken in order to select the best virtualization approach for specific application requirements. The most effective decision points in the sequence are presented for determining which virtualization technology should be used. When considering virtualization for multiple applications, readers should iterate through the entire process individually for each type of application.